Islamic Studies Receptions Among State Madrasah Aliyah Students in West Sulawesi at PTKIN Institutions - Sulkifli; Saleh, Muhammad; Masyhadiah; Yusriah (STAIN Majene, 2025)
Abstract This research aims to explore the receptions of students from State Madrasah Aliyah in West Sulawesi regarding Islamic studies at PTKIN (State Islamic Higher Education Institutions). This study employs a qualitative methodology with a reception approach to gather insights. The findings indicate that students predominantly perceive PTKIN as an institution primarily focused on Islamic studies, which influences their university preferences. The study also highlights the reception of Islamic studies programs by MAN students at PTKIN is notably positive. Students' reception of these programs aligns with the core mission of PTKIN, which is to deepen knowledge in Islamic sciences. This alignment between PTKIN's intended message and the students' understanding suggests a strong concordance between the encoding and decoding processes. The findings suggest a need for PTKIN to better communicate the diversity of programs available and enhance their appeal to MAN graduates. Keywords: Reception, PTKIN, Islamic Studies